2018
DOI: 10.1634/theoncologist.2017-0629
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Characterization of Young Chinese Patients with Lung Adenocarcinoma Identified a Distinctive Genetic Profile

Abstract: Further investigation is needed to understand the genomics and clinical characteristics of young patients with lung adenocarcinoma. In the present study, hybrid capture-based next-generation sequencing assays were used to identify targeted genetic alterations in young lung adenocarcinoma patients. Young patients with lung adenocarcinoma, aged less than 45 years, harbored a higher frequency of and genetic alterations compared with patients aged more than 46 years. Dramatically, concurrent / mutations were much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 28 publications
4
64
5
Order By: Relevance
“…However, other studies revealed that the second‐generation TKI afatinib was more active in patients with NSCLC who harbored certain types of uncommon EGFR mutations, especially G719, L861Q, and S768I , which indicated that accurate detection of uncommon EGFR mutations would help patients with NSCLC to select targeted therapeutic drugs more precisely. Besides, it was noteworthy that comutation of EGFR and TP53 was frequently found in female patients in this study; another study showed that it was more likely to occur in young patients <45 years of age . At the same time, the common mutation of EGFR and TP53 is correlated with a poor prognosis .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, other studies revealed that the second‐generation TKI afatinib was more active in patients with NSCLC who harbored certain types of uncommon EGFR mutations, especially G719, L861Q, and S768I , which indicated that accurate detection of uncommon EGFR mutations would help patients with NSCLC to select targeted therapeutic drugs more precisely. Besides, it was noteworthy that comutation of EGFR and TP53 was frequently found in female patients in this study; another study showed that it was more likely to occur in young patients <45 years of age . At the same time, the common mutation of EGFR and TP53 is correlated with a poor prognosis .…”
Section: Discussionmentioning
confidence: 51%
“…We used 900× depth sequencing and found a total of 56 different types of uncommon EGFR mutations, which could be observed in the extracellular domain (12.3%), transmembrane domain (1.9%), exon 18 (nucleotide‐binding loop, 35.7%), exon 19 (4.5%), exon 20 (16.2%), exon 21 (activation loop, 20.1%), autophosphorylation domain (5.8%), and structure variations (3.2%). Some uncommon EGFR mutations with high incidence (more than 10 cases) included L861 M/Q/R, G719A/C/S, S768I, and E709A/K, which have been described previously . L861Q, G719X, and S768I were EGFR mutations with weak activities; the median PFS of patients who received EGFR TKIs as first‐line treatment was 7.6 months, 8.2 months, and 3.4 months, respectively, which was significantly shorter than that in patients with common EGFR mutations (exon 19 deletion and L858R) .…”
Section: Discussionmentioning
confidence: 77%
“…According to previous studies, TP53 mutations could be found in 30%-72% of all EGFR-mutated NSCLCs and 25%-56% of ALK-positive NSCLCs, predominantly in smokers [26,27] and the younger patients [28] , but were rare in patients with other less common targeted mutations like KRAS mutation/ROS1 re-arrangement/RET re-arrangement [29]. Previous studies have suggested that TP53 concurrent mutation might adversely impact the survival of patients with advanced NSCLC treated with EGFR-TKIs or ALK-TKIs for oncogenic EGFR or ALK mutations [30][31][32][33].…”
Section: Introductionmentioning
confidence: 90%
“…Meanwhile, over-activation of the ALK signaling such as ALK amplification, up-regulation of bypass signaling pathways might be chief culprits that confer primary resistance to ALK-TKIs [20,21].In NSCLC, TP53 mutations are the most common co-occurring events with driver oncogenes. According to previous studies, TP53 mutations could be found in 30%-72% of all EGFR-mutated NSCLCs and 25%-56% of ALK-positive NSCLCs, predominantly in smokers [23,24] and the younger patients [25] , but were rare in patients with other less common targeted mutations like KRAS mutation/ROS1 rearrangement/RET re-arrangement [26].…”
Section: Nsclcmentioning
confidence: 94%